TANTANGAN DAN SOLUSI AKUNTAN BERPRAKTIK DALAM MENGHADAPI RI 4.0 (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2021)
This research  aims to know the challenges faced by practicing accountants, as well as to know the alternative solutions offered in the face of  IR4.0. This research uses the Analytic Network Process method. The respondents consist of those who know about practicing accountants and the IR 4.0. The results of the study reveal that there are internal and external challenges for practicing accountants. Accountants' individual character factors who are not familiar with technology; HR capabilities in the field of technology, is an internal challenge. Whereas the external challenges are, digital technology is getting more sophisticated; digital technology is included in the realm of accounting. While the alternative solutions offered are as follows; Internal solutions; sustainable human resources development; individual accountants become familiar with technology. While the external solutions are; follow digital technology and apply it; improve competence in big data analysis; and keep up with technological advances.
Keywords: Practicing Accountants; Industrial Revolution 4.0 (IR 4.0); Analytic Network Process